Relationships Between Poor Health and Calories From Fat Among Commercial Truck Drivers. Issue 11 (November 2019) - Okorie, Onwuka; Thiese, Matthew S.; Murtaugh, Maureen A.; Sheng, Xiaoming; Handy, Rodney; Hegmann, Kurt
Abstract : Objective: Commercial motor vehicle (CMV) drivers face many challenges to their health, including poor diet, disease, and crash risk. This study quantifies relationships between the percentage of calories from fat (PCF) and markers of poor health, many of which are associated with increased crash risk. Methods: Cross-sectional data from 790 CMV drivers were analyzed. PCF were estimated using the National Cancer Institute Percentage Energy from Fat Screener. Adjusted odds ratios (ORs) were calculated. Results: The highest category of PCF (>38.2%) was statistically significantly more likely to not exercise (OR = 2.08), have sleep apnea (OR = 2.31), snore (OR = 1.90), smoke (OR = 2.28), and use alcohol (OR = 1.87) after adjustments. Conclusion: Meaningful relationships between PCF and poor health indicators exist. These indicators may provide an intervention to improve the health and safety of CMV drivers.